The Influence of Green Training on Green Supply Chain Management Practices and Firm’s Performance - Wongthongchai, Jirawat; Saenchaiyathon, Krittapha (International Journal of Engineering and Technology, 2019)
This research was conducted to study the influence of green training on green supply chain management (GSCM) and firmâ€™s performance. By using institutional theory to explain the driving force of reducing the impact of environmental processes on the firm. The population of this study are firms that have been certified to ISO 14000 which is an environmentally relevant standard. The research proposes are to study 1) top management support, competitor pressure, and customer pressure that influence on green supply chain management practices; 2) green training that influence on green supply chain management practices; 3) the influence of green supply chain management practices and green training on the firmâ€™s performance. Systematic random was used, Questionnaires were distributed . Structure equation model technique was employed for data analysis.In data analysis by SEM technique, top management support, competitor pressure, customer pressure, and green training play positive effect to the GSCM practices with statistical significant. Furthermore, GSCM practices play positive effect to the firmâ€™s performance with statistical significant. Under the literature foundation, customer pressure, top management support is primary factor to achieve GSCM practices and capabilities for establishment the firmâ€™s performance. To do further on GSCM practices more efficiency, a firm is able to have green training. The literature review also showed that special training must be aligned with improvements in the organizational process. It is evident that green training works through green supply chain management and the relationship between green training is not clear. The results of this study showed that the training did not have correlation to the performance but was related to green supply chain management practices.Â